HUBUNGAN USIA DENGAN INSIDENSI PENYAKIT HIPERTENSI PADA MASYARAKAT DI PUSKESMAS JEULINGKE BANDA ACEH - Rahmad Rahmad; Suriatu Laila (Jurnal Sains Riset, 2021)
Hypertension is the term used to describe high blood pressure. When heart beats, it pushes blood through arteries to the rest of body. When the blood pushes harder against the walls of arteries, the blood pressure goes up. With aging, there is a progressive loss of the visco-elastic properties of conduit vessels, increased atherosclerotic arterial disease, and hypertrophy and sclerosis of muscular arteries and arterioles. Aging also causes progressive decline in the ability of the kidneys to excrete salt loads efficiently, resulting in higher blood pressure levels. This research is a observational analytic based cross sectional study and aims to determine relationship of age to the incidence of hypertension in Puskesmas Jeulingke Banda Aceh. Data collection was conducted on 96 respondents from April to July 2017 at Puskesmas Jeulingke Banda Aceh. The data collected shows that most respondents are in 45 years old, which is accounted for 52 people (54.2%), the majority work as marketeers which is accounted for 29 people (30.2%), and high school is highest level of education they have attended in majority, which is accounted for 40 people (41.7%). The results show that there is a relationship of age with the incidence of hypertension in the Puskesmas Jeulingke Banda Aceh with ρ-value = 0,000 (0,05). The authors suggest to Puskesmas Jeulingke Banda Aceh to improve community knowledge through counseling in order to increase people's knowledge about hypertension, encourage people to check their blood pressure regularly and promote healthy lifestyles.Keywords: age, incidence of hypertension